Nontargeted metabolomics study and pharmacodynamic evaluation of bidirectional fermentation for Ganoderma lucidum with Marsdenia tenacissima - Li, Runtian; Zhang, Zhiguang; Su, Xinxin; Yu, Jiaoneng; Lu, Lin; Liu, Tongxiang (Frontiers in Pharmacology, 2022)
Lung cancer is one of the malignant tumors with the fastest incidence rate and mortality growth and the greatest threat to human health and life. Marsdenia tenacissima is an antitumor of Chinese medicine. However, Marsdenia tenacissima has low bioavailability in the human body and most of its main active substances are aglycones, such as Tenacigenin A, Tenacigenin B. This study aims to produce biotransformation products rich in pungent saponins by using Marsdenia tenacissima as a fermentation medium of Ganoderma lucidum. Non-targeted metabolomics analysis was carried out on the fermentation products after the optimization process. A total of 249 differential metabolites were detected, and the content of saponins increased from 0.1 % to 0.41 % and most of them were tenacigenin. Furthermore, the biotransformation of C21 steroidal glycosides in Marsdenia tenacissima was the central reaction in this fermentation process. Pharmacodynamics resewed that the anticancer effect of Marsdenia tenacissima was significantly enhanced after fermentation, mainly through inhibiting the growth and apoptosis of cancer cells.